2015 IEEE 35th International Conference on Electronics and Nanotechnology (ELNANO) 2015
DOI: 10.1109/elnano.2015.7146876
|View full text |Cite
|
Sign up to set email alerts
|

Hollow-cathode plasma-assisted atomic layer deposition: A novel route for low-temperature synthesis of crystalline III-nitride thin films and nanostructures

Abstract: -Hollow cathode plasma-assisted atomic layer deposition is a promising technique for obtaining III-nitride thin films with low impurity concentrations at low temperatures. Here we report our efforts on the development of HCPA-ALD processes for III-nitrides together with the properties of resulting thin films and nanostructures. The content will further include nylon 6,6/GaN core/shell and BN/AlN bishell hollow nanofibers, proof-of-concept thin film transistors and UV photodetectors fabricated using HCPA-ALD-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Deposited films on Si (100) were polycrystalline with hexagonal (002) preferred orientation, however, the same preferred orientation was not observed on c-plane sapphire substrates [131]. Use of HCPEALD was found to be quite effective in decreasing the oxygen impurity within GaN films by more than two orders of magnitude [131][132][133][134][135][136]. Motamedi et al reported PEALD of GaN with Ga(C 2 H 5 ) 3 and forming gas mixture (95% N 2 /5% H 2 ) plasma reactants at 275 °C.…”
Section: Nitridesmentioning
confidence: 96%
“…Deposited films on Si (100) were polycrystalline with hexagonal (002) preferred orientation, however, the same preferred orientation was not observed on c-plane sapphire substrates [131]. Use of HCPEALD was found to be quite effective in decreasing the oxygen impurity within GaN films by more than two orders of magnitude [131][132][133][134][135][136]. Motamedi et al reported PEALD of GaN with Ga(C 2 H 5 ) 3 and forming gas mixture (95% N 2 /5% H 2 ) plasma reactants at 275 °C.…”
Section: Nitridesmentioning
confidence: 96%
“…GaN (PE-ALD) [1,8,10,11,13,14,16,20,21,30,35] GaN devices (PE-ALD) [2,4,10,11,17] Nanofibers (PE-ALD) [5,[9][10][11]] Nanostructures (ALD) [18,21] AlGaN (PE-ALD) [1,3] AlN (PE-ALD) [1,5,[19][20][21]29,32] BN (PE-ALD) [5,6,11] InN (PE-ALD) [10,11,15,[19][20][21]33,34] BInN and BGaN (PE-ALD)…”
Section: Materials (And Process) Referencementioning
confidence: 99%